FAKTOR INDIVIDU DAN KEPUASAN KERJA DENGAN PENDAPATAN TENAGA MEDIS SPESIALIS DI RUMAH SAKIT UMUM DAERAH SULTAN SULAIMAN KABUPATEN SERDANG BEDAGAI - Selamat Hartono; Arifah Defi Fitriani; Miskah Afriany (Jurnal Ilmiah Kesehatan, 2024)
Purpose: The purpose of this research is to analyze the influence of individual and psychological factors (job satisfaction) performance of medical specialists on income. Methods This type of research is a quantitative study with a descriptive design. This research was conducted at the General Hospital of the Sultan Sulaiman area, Serdang Bedagai Regency. The sample used is the whole of the total population of 40 specialist doctors. Results: The results of the bivariate analysis showed that there was no relationship between age and income of specialist doctors (p = 0.307), there was no relationship between gender and income of specialist doctors (p = 0.766), there was no relationship between work period and income of specialist doctors (p = 0.319), no There is a relationship between employment status and income of specialist doctors (p = 0.454), there is a relationship between Psychological Factors (Job Satisfaction) and income of specialist doctors (p = 0.016). Conclusion: It is hoped that hospital leaders need socialization or efforts to increase commitment to the organization and doctors' understanding of the vision and mission of the hospital and for specialist doctors to think positively about changes in existing policies, only to improve the quality and achieve the hospital's vision and mission so that they will impact on the welfare of employees and doctors.